SINGAPORE-AUSTRALIA DIGITAL ECONOMY AGREEMENT (SADEA) TAHUN 2020 - Santoso, Sagit Hartono; Anggraini, Deria (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The purpose of this study is to determine the form of implementation of the Singapore-Australia Digital Economy Agreement (SADEA) cooperation in 2020. The method used in this study is a qualitative method with a descriptive research type. The data collection technique used is a literature study in the form of official government websites, books, journal articles, research reports, and media articles. The theory used is techno-nationalism, which is a theory that approaches countries that carry out technology governance, implement it and influence the global market. The results of the study explain that the formation of cooperation between Singapore and Australia in improving the digital economy. Increasing the digital economy is carried out by creating an international environment that supports its development. Technological developments encourage countries to adopt sophisticated technology in their economic activities, conduct digital trade negotiations, and work together to create a series of regulations in the implementation process. By cooperating through SADEA, Singapore and Australia strive to create a digital economic environment that is safe, trusted by the community, and based on rules.